The Interplay of Rogue and Clustered Ryanodine Receptors Regulates Ca2+ Waves in Cardiac Myocytes - Chen, Xudong; Feng, Yundi; Huo, Yunlong; Tan, Wenchang (Frontiers in Physiology, 2018)
Ca2+ waves in cardiac myocytes can lead to arrhythmias owing to delayed after-depolarisations. Based on Ca2+ regulation from the junctional sarcoplasmic reticulum (JSR), a mathematical model was developed to investigate the interplay of clustered and rogue RyRs on Ca2+ waves. The model successfully reproduces Ca2+ waves in cardiac myocytes, which are in agreement with experimental results. A new wave propagation mode of “spark-diffusion-quark-spark” is put forward. It is found that the rogue RyRs greatly increase the initiation of Ca2+ sparks, further contribute to the formation and propagation of Ca2+ waves when the free Ca2+ concentration in JSR lumen ([Ca2+]lumen) is higher than a threshold value of 0.7 mM. Computational results show an exponential increase in the velocity of Ca2+ waves with [Ca2+]lumen. In addition, more CRUs of rogue RyRs and Ca2+ release from rogue RyRs result in higher velocity and amplitude of Ca2+ waves. Distance between CRUs significantly affects the velocity of Ca2+ waves, but not the amplitude. This work could improve understanding the mechanism of Ca2+ waves in cardiac myocytes.